PPO.09 The relationship between birthweight and brachio-femoral pulse wave velocity in early infancy: findings from a British birth cohort (Baby VIP study). (9th June 2014) - Alwan, NA; Cade, JE; Greenwood, DC; McArdle, HJ; Ciantar, E; Simpson, NAB
Abstract : Background: In adults, pulse wave velocity (PWV) is regarded as a predictor of cardiovascular disease. 1 However, associations in infants are not well established. One study has linked neonatal aortic PWV, at 1–3 days, with birthweight and maternal blood pressure. 2 Aim: To examine the relationship between infant brachio-femoral PWV and size at birth. Methods: Baby VIP study recruited 362 newborn babies from the Leeds Teaching Hospitals Trust, including 64 small for gestational age (SGA) (18%). PWV was measured non-invasively from each baby at a follow-up home visit 2–6 weeks after recruitment, using the Vicorder kit. Birthweight and other covariables were collected from the delivery and antenatal medical notes. Individualised birthweight centiles were calculated using the GROW-Centile calculator taking into account maternal weight, height, parity, ethnicity, gestational age and baby's sex. 3 Results: Mean birthweight was 3329 g (standard deviation [sd] 632). Mean infant PWV was 6.7 m/s (sd 1.3). In univariable analysis, SGA babies had, on average, lower PWV by 0.4 m/s (95% confidence interval 0.0, 0.9, P = 0.04). This association persisted after adjusting for pregnancy factors including maternal smoking, pre-eclampsia, gestational diabetes, blood pressure at booking and 36 weeks, and infant factors including type of feeding, baby's age, position and whether asleep or awake at the time of measurement (0.5 m/s lower, 0.1, 0.9, P = 0.02). Conclusion: This study has demonstrated the feasibility and acceptability of measuring PWV in early infancy. SGA was associated with a lower PWV. These findings support the evidence linking SGA with cardiovascular indicators, even very early in life.